LOCAL CULTURAL FESTIVAL OF PRINGGASELA LOMBOK: AN ANALYSIS OF THE WASATHIYAH ISLAMIC PERSPECTIVE - Alinah, Amri Malik Aziz Rahman (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
This research aims to review the Pringgasela Cultural Festival as a representation of a local cultural preservation combined with the Wasathiyah Islamic values. A qualitative approach through an ethnographic study case was used to comprehend social dynamics, innovation diffusion processes, and symbolic meanings that emerged in the festival. Data were obtained from observation, interview, and field documentation. The result showed that festival becomes a space for cultural preaching that brings together both tradition and Islamic spirituality in harmony. The values of moderation (tawassuth), balance (tawazun), and innovation (tahawwur wa ibtikar) are reflected in the creative packaging of cultural activities, yet remain rooted in the Islamic identity of the Pringgasela society. Through Roland Barthes’ semiotic analysis, this festival is understood as a cultural text producing Islamic narratives of Lombok that are moderate, open, and adaptive to social change.